2021
DOI: 10.3390/horticulturae7110428
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Anti-Microbial Activity of Hog Plum (Spondias mombin L.) Peel Oil Extracted from Different Regions of Tropical Climates

Abstract: The hydro-distilled essential oil of hog plum peel may be used for enhancing the flavor and taste of food products as well as for hiding the unpleasant odor of drugs. Thus, the waste peels of Spondias mombin appear to have economic importance. To find out the chemical composition and anti-microbial properties of hog plum peel oil, the samples were collected from different regions of Bangladesh for extraction and identification of volatile compounds by GC-MS, where dichloromethane was used as an extraction solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…The essential oil of S. mombin fresh and dried leaves were assayed for their potency against brine shrimps. The fresh leaf volatile oil was more active than that obtained from dried leaves, with LC50 values of 0.01 and 4.78 μg/mL, respectively [30] According to Plabon et al, 2021, the volatile oil of the peel oil showed the highest zone of inhibition against the Aspergillus niger (11.63 ± 0.0003 mm) and Penicillium oxalicum (13.67 ± 1.97 mm [34]. It is suggested that the potency shown by the essential oil of S. mombin could be due to the presence of major chemical components in the oil.…”
Section: Antimicrobial Activitymentioning
confidence: 98%
“…The essential oil of S. mombin fresh and dried leaves were assayed for their potency against brine shrimps. The fresh leaf volatile oil was more active than that obtained from dried leaves, with LC50 values of 0.01 and 4.78 μg/mL, respectively [30] According to Plabon et al, 2021, the volatile oil of the peel oil showed the highest zone of inhibition against the Aspergillus niger (11.63 ± 0.0003 mm) and Penicillium oxalicum (13.67 ± 1.97 mm [34]. It is suggested that the potency shown by the essential oil of S. mombin could be due to the presence of major chemical components in the oil.…”
Section: Antimicrobial Activitymentioning
confidence: 98%
“…The hydrodistilled essential oil of S. mombin peel showed antimicrobial activities against the food-borne pathogenic bacteria (Salmonella spp., Staphylococcus aureus, and Escherichia coli) and fungi (A. niger, and P. oxalicum). According to Plablon et al [78], the antimicrobial activity of the extract can be related to the presence of monoterpenes, mainly terpene hydrocarbons.…”
Section: Spondias Mombinmentioning
confidence: 99%
“…High-resolution liquid chromatography-mass spectrometry (LC-HRMS) [25] and nuclear magnetic resonance (NMR) spectroscopy [26] are some of the commonly used analytical tools in metabolomics. Natural products have been reported for various biological activities, including antiinflammatory [27], antioxidant [28], antibacterial [29], antiparasitic [30], antifungal [31], analgesic [32], anti-atherogenic [33], antidiabetic [34], and antiproliferative properties [35]. In recent years, several studies have reported that natural products also have anti-acaricidal activity with great application potential.…”
Section: Introductionmentioning
confidence: 99%